Fukushima Wastewater Release and its Profound Impact on the Fishing Industry - Liu, Daniel (Transactions on Environment, Energy and Earth Sciences, 2024)
This research delves into the significant effects of releasing Fukushima wastewater in August 2023 on the fishing industry, using linear and multivariate regression models for a thorough analysis computed by SPSS. Post-Fukushima, the introduction of radioactive wastewater into the marine environment has raised alarm, particularly regarding the repercussions for marine biodiversity and the crucial fishing sector in the Northern Pacific. Analyzing data from the North Pacific Anadromous Fish Commission and Japan’s fishery exports, with the aid of a Tsinghua University simulation, this study evaluates the impact of radioactive discharge on marine ecosystems and fishing economies. Findings indicate a clear negative impact on fisheries, affecting not just Japan but also other Northern Pacific regions. Statistical models confirm substantial environmental and economic detriments to the fishing sector stemming from contamination. This work not only highlights the immediate fallout from the Fukushima incident but also provides foresight into enduring effects for Japan and other involved countries. Results accentuate the urgent need for robust disaster management and strategies to maintain ecological and industry health, vital for sustaining community economies).